A Selective Approach to Establishing a Human Rights Mechanism in Southeast Asia : the Case for a Southeast Asian Court of Human Rights. - Phan, Hao Duy (BRILL, 2012)
This book proposes a selective approach for states with more advanced human rights protection to establish a human rights court for Southeast Asia. It argues the inclusive approach currently employed by ASEAN to set up a human rights body covering all member states cannot produce a strong regional human rights mechanism. The mosaic of Southeast Asia reveals great diversity and high complexity in political regimes, human rights practice and participation by regional states in the global legal human rights framework. Cooperation among ASEAN members to protect and promote human rights remains li.